Brazilian National Network of Alternative Methods (RENAMA) 10th Anniversary: Meeting of the Associated Laboratories, May 2022 - Ivan de Ávila, Renato; Fentem, Julia; Villela, Izabel; Somlo, Debora; Fusco Almeida, Ana Marisa [UNESP]; Mendes-Giannini, Maria José S. [UNESP]; Di Pietro Micali Canavez, Andrezza; Bosquetti, Bruna; Catarino, Carolina Motter; Schuck, Desiree Cigaran; Valadares, Bruna Nardy; Facchini, Gustavo; et al. (SAGE Publications, 2024)
The Brazilian National Network of Alternative Methods (RENAMA), which is linked to the Ministry of Science, Technology and Innovation, is currently comprised of 51 laboratories from CROs, academia, industry and government. RENAMA’s aim is to develop and validate new approach methodologies (NAMs), as well as train researchers and disseminate information on their use — thus reducing Brazilian, and consequently Latin American, dependence on external technology. Moreover, it promotes the adoption of NAMs by educators and trained researchers, as well as the implementation of good laboratory practice (GLP) and the use of certified products. The RENAMA network started its activities in 2012, and was originally comprised of three central laboratories — the National Institute of Metrology, Quality and Technology (INMETRO); the National Institute of Quality Control in Health (INCQS); and the National Brazilian Biosciences Laboratory (LNBio) — and ten associated laboratories. In 2022, RENAMA celebrated its 10th anniversary, a milestone commemorated by the organisation of a meeting attended by different stakeholders, including the RENAMA-associated laboratories, academia, non-governmental organisations and industry. Ninety-six participants attended the meeting, held on 26 May 2022 in Balneário Camboriú, SC, Brazil, as part of the programme of the XXIII Brazilian Congress of Toxicology 2022. Significant moments of the RENAMA were remembered, and new goals and discussion themes were established. The lectures highlighted recent innovations in the toxicological sciences that have translated into the assessment of consumer product safety through the use of human-relevant NAMs instead of the use of existing animal-based approaches. The challenges and opportunities in accepting such practices for regulatory purposes were also presented and discussed.
Keywords: Brazil; Brazilian National Network of Alternative Methods; conference NAMs; Network to Alternative Methods; new approach methodologies; next-generation risk assessment